2007
DOI: 10.1021/la701789n
|View full text |Cite
|
Sign up to set email alerts
|

Preparation Parameter Development for Layer-by-Layer Assembly of Keggin-type Polyoxometalates

Abstract: Polyoxometalates possess many useful properties for electrochemical catalysis. These molecule-size clusters can be assembled into thin films through the layer-by-layer method. In this study, we determined a cluster concentration range within which layer-by-layer (LbL) films have been successfully fabricated. We also find the influence of salt added to the deposition solutions. In an attempt to understand the self-assembly process at the molecular level, thermodynamic arguments, derived from complexation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 37 publications
7
50
0
Order By: Relevance
“…The high permeability may be originated from a moderate delamination of films and less-stratified microstructure. Compared to the PMo 12 surface coverage trend, 60 the diffusion of [Fe(CN) 6 ] 3-/4-couple into the multilayer assembly seems independent of the PMo 12 loading.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The high permeability may be originated from a moderate delamination of films and less-stratified microstructure. Compared to the PMo 12 surface coverage trend, 60 the diffusion of [Fe(CN) 6 ] 3-/4-couple into the multilayer assembly seems independent of the PMo 12 loading.…”
Section: Resultsmentioning
confidence: 86%
“…PMO 12 PDDA multilayer films were deposited according to our recently published procedure. 60 APTES modified ITO slides were dipped in PMO 12 solution (10 min) and PDDA solution (10 min) in an alternating fashion for 10 consecutive times, between each dipping the slides were exposed to three consecutive water baths for 5 seconds each. Electrochemical cell and the measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being inorganic oligomeric aggregates, POMs can not only form insoluble complexes with many positive charged polymers, [18][19][20][21][22] but can also construct coacervates with zwitterionic proteins through electrostatic interactions. [20,23,24] The obtained complexes are usually not stable in solution, and will eventually precipitate out from the system in the absence of proper stabilizers or surfactants.…”
Section: Preparation Of Gelatin/hm Hybrid Nanoparticlesmentioning
confidence: 99%
“…It is believed that Keggin-type Polyoxometalates (POMs) in an aqueous solution could effectively assist the electrochemical oxidation of carbon monoxide (CO) to carbon dioxide (CO 2 ) [23,24]. The transition metal-substituted polyoxometalates (TMSP) have the potential wider application due to their better performance including catalytic reactivity [25], the possibility of multiple electron transfer [26], ªpseudo liquid phaseº behavior [27], and extremely versatile inorganic building blocks for the construction of organic-inorganic composites [28]. It has been observed that the electrocatalytic activities of Pt catalysts are enhanced when supported by TMSP [29,30], which suggests that it is possible for them to be employed as catalysts in the anodic methanol oxidation process.…”
Section: Introductionmentioning
confidence: 99%